The Relationship of Anxiety and Self-Harm Tendencies in Final Year Students - Widihastuti, Diva Peni Agustin; Oktaviana, Wita (Indonesian Journal of Global Health Research, 2024)
Final year students often experience high academic pressure which can cause anxiety, if not handled it can lead to self-harm behavior. Therefore, this study aims to determine the relationship between anxiety and self-harm tendencies in final year students at the Faculty of Health Sciences, Muhammadiyah University of Surakarta. The instruments used in this research were the Zung Self Rating Anxiety Scale and Self-Harm Inventory with validity and reliability values between 0.397-0.906. Respondents in this study involved final year students from the Faculty of Health Sciences, Muhammadiyah University of Surakarta, totaling 246 students using purposive sampling techniques. The research results show that there is a relationship between anxiety and self-harm behavior in final year students, with a significant value (p-value) = 0.000, which shows a weak correlation with a value of r = 0.493. Using the Spearman Rho test, the results of research conducted by researchers show a significant relationship between anxiety and self-harm tendencies in final year students. In conclusion, the higher the level of anxiety, the greater the possibility of students committing self-harm.